Contributions of the mindfulness practice for the development of therapeutic skills (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
In the clinical context, therapist’s behaviors and the relationship that he/she establishes with the client are notonly relevant but may facilitate or prevent the development of the therapeutic process. From a narrative review,the present study aimed to present some contributions of the mindfulness practice for the development oftherapeutic skills. Thus, from the conceptual foundations of mindfulness and clinical practice in psychology,it was discussed how the mindfulness practice can facilitate the development of therapeutic skills. The fiveelements model proposed by Baer, Smith, Hopkins, Krietemeyer and Toney (2006), Zarbock et al. (2015), andFulton's (2016) considerations on mindfulness skills were used. It was pointed out that learning mindfulnesspractices can benefit clinical services by strengthening the therapeutic rapport between client and therapist, aswell as creating a non-punitive audience for events that occur during the therapeutic process throughacceptance and “beginner’s mind” strategies.
Keywords: mindfulness; therapeutic skills; clinical practice